Natural pest control diversity on Oryza sativa L. (Poaceae) managed in organic and conventional cultivation systems in Desa Tegal Sari, Ogan Komering Ulu Timur, South Sumatera - Gilang Putra Bintang; Weri Herlin; Chandra Irsan; Oktaviani (Bioma, 2025)
Natural controls, such as predators and parasitoids, play a crucial role in maintaining the stability of agricultural ecosystems through biological pest control mechanisms. On the rice agriculture systems, we propose to evaluate the diversity and abundance of natural controls in organic and conventional rice cultivation systems in Tegal Sari Village, Ogan Komering Ulu Timur Regency, South Sumatra. Observations were conducted using a systematic survey method employing various types of insect traps, with organism identification carried out to the level of type. This research is expected to contribute to both academic and practical domains. The results revealed the presence of 10 arthropod species from four orders, including Araneae, with dominant species such as Pardosa pseudoannulata, Tetragnatha extensa, Tetragnatha montana, Tetragnatha sp., Tigrosa annexa, and Zygiella are always higher on the organic rice agricultural system compared to the conventional system. The diversity analysis indicated that sweep nets were more effective in capturing natural controls compared to other traps, with a Shannon-Wiener diversity index value of 2.17, suggesting moderate diversity. These findings emphasize that organic farming supports biodiversity conservation and provides a scientific foundation for the development of pest management strategies.